Rate-dependent micromechanical model applied to wave propagation through rough interfaces - Marangos, Orestes; Misra, Anil S. (My University, 2007)
Asperity contact viscosity can result in a rate dependent behavior at the interfaces between two rough solids. The authors have developed a micromechanical methodology for rough interfaces to relate the asperity behavior to the overall interface behavior. This methodology is applied to determine the rate-dependent effective normal and shear stiffness of the interface. The calculated complex-valued stiffnesses are used to investigate plane wave propagation behavior through interfaces utilizing the imperfectly bonded interface model © 2007 IEEE.
Keywords: Interfaces; Micromechanics; Reflection coefficient; Transmission coefficient; Viscoelasticity